Paediatric applied respiratory physiology – the essentials. Issue 7 (July 2017) - Bhalla, Anoopindar; Khemani, Robinder G.; Newth, Christopher J.L.
Abstract: General paediatricians will frequently encounter children with a variety of respiratory abnormalities. A basic knowledge of respiratory physiology, pathophysiologic derangements during common paediatric disease states and appropriate assessment of abnormalities is essential to properly care for children with respiratory disease. This review will give an overview of normal respiratory physiology and how to assess the efficiency of gas exchange. It will also discuss common methods of respiratory monitoring including pulse oximetry, carbon dioxide monitoring, pulmonary function tests and respiratory effort and capacity tests. Finally, paediatric diseases will be used to illuminate the intersection between pathophysiology, clinical symptoms and monitoring capabilities.